2023
DOI: 10.3389/fendo.2023.1110489
|View full text |Cite
|
Sign up to set email alerts
|

Central node dissection in papillary thyroid carcinoma in the era of near-infrared fluorescence

Abstract: The most common site of lymph node metastases in papillary thyroid carcinoma is the central compartment of the neck (level VI). In many patients, nodal metastases in this area are not clinically apparent, neither on preoperative imaging nor during surgery. Prophylactic surgical clearance of the level VI in the absence of clinically suspicious lymph nodes (cN0) is still under debate. It has been suggested to reduce local recurrence and improve disease-specific survival. Moreover, it helps to accurately diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Understanding the extent and location of LNM is crucial for developing treatment plans. Studies have confirmed that PTC patients with CLNM have a lower survival rate and a higher risk of recurrence ( 4 , 5 ). Therefore, it has been suggested that prophylactic central lymph node dissection can identify lymph node lesions and potentially reduce the risk of disease recurrence ( 6 ).…”
Section: Introductionmentioning
confidence: 94%
“…Understanding the extent and location of LNM is crucial for developing treatment plans. Studies have confirmed that PTC patients with CLNM have a lower survival rate and a higher risk of recurrence ( 4 , 5 ). Therefore, it has been suggested that prophylactic central lymph node dissection can identify lymph node lesions and potentially reduce the risk of disease recurrence ( 6 ).…”
Section: Introductionmentioning
confidence: 94%
“…Various factors contribute to the risk of post-thyroidectomy hypocalcemia, including perioperative parathyroid hormone (PTH) levels, preoperative vitamin D (VD) deficiency, and potential parathyroid gland damage or removal during surgery ( 3 ). Recently, the introduction of new intraoperative modalities aimed at preserving intraoperative parathyroid function has been reported ( 4 , 5 ). The literature also discusses using preoperative VD or calcium (Ca) supplementation ( 1 , 3 , 6 ), as well as various postoperative Ca management strategies ( 7 , 8 ), to address this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors contribute to the risk of post-thyroidectomy hypocalcemia, including perioperative parathyroid hormone (PTH) levels, preoperative vitamin D (VD) de ciency, and potential parathyroid gland damage or removal during surgery [3]. Recently, the introduction of new intraoperative modalities aimed at preserving intraoperative parathyroid function has been reported [4,5]. The literature also discusses using preoperative VD or calcium (Ca) supplementation [1,3,6], as well as various postoperative Ca management strategies [7,8], to address this issue.…”
Section: Introductionmentioning
confidence: 99%
“…PTH is crucial in regulating Ca concentrations, both directly and indirectly by producing 1,25dihydroxyvitamin D (1,25(OH)2D). However, the difference in the half-life of PTH and 1,25(OH)2D (3)(4)(5) min for the former and 5-20 h for the latter) [17 18 19], suggests that 1,25(OH)2D is not completely subordinate to PTH in in uencing Ca metabolism. While both PTH and 1,25(OH)2D are vital for managing Ca concentration after thyroidectomy, research on the role of 1,25(OH)2D is very limited.…”
Section: Introductionmentioning
confidence: 99%